2005
DOI: 10.3122/jabfm.18.5.401
|View full text |Cite
|
Sign up to set email alerts
|

Improving Female Preventive Health Care Delivery Through Practice Change: An Every Woman Matters Study

Abstract: Background:The levels of breast and cervical cancer screening in Nebraska primary care remain suboptimal despite awareness of their importance, and despite implementation of the Every Woman Matters program to assist low-income women. The GAPS model was used to develop a practice-based intervention to identify and reduce barriers to delivery of breast and cervical cancer screening services.Methods: Seven primary care practices actively participated in this multimethod case study. A research nurse collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…There is ample evidence that primary prevention measures are underused in general practice. [703][704][705] Although adherence rates to national recommendations for the treatment and control of cardiovascular risk factors are improving, there is still a large treatment gap. 95,706,707 Across the United States, the adherence rate for the treatment of hypertension is 61%; only 35% of those treated have their hypertension under control.…”
Section: Preventive Health Services/strategies To Improve Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence that primary prevention measures are underused in general practice. [703][704][705] Although adherence rates to national recommendations for the treatment and control of cardiovascular risk factors are improving, there is still a large treatment gap. 95,706,707 Across the United States, the adherence rate for the treatment of hypertension is 61%; only 35% of those treated have their hypertension under control.…”
Section: Preventive Health Services/strategies To Improve Adherencementioning
confidence: 99%
“…711,712 A combination of techniques is usually necessary to improve adherence, including physician education, addressing physician inertia, audit and feedback of practice patterns, physician profiling, patient prompts, and outreach visits. 703,708,[711][712][713] Some general strategies to improve adherence in the outpatient setting, although relatively costly, are more consistently effective. These include computer-based clinical reminder systems, electronic medical records, 714,715 and tailored, multifaceted programs.…”
Section: Preventive Health Services/strategies To Improve Adherencementioning
confidence: 99%
“…Successfully changing practice behavior involves a team effort among providers and clinic staff, flexibility and willingness to change, and interventions tailored to each practice (Dietrich, Woodruff, & Carney, ; Goodwin et al, ). The preventive care‐focused goal setting/assessment/plan/start‐up (GAPS) model incorporates these concepts (Dietrich et al) and has been successfully applied to develop a practice‐based intervention to increase breast and cervical cancer screening services (Backer, Geske, McIlvain, Dodendorf, & Minier, ). The approach is a four‐step continuous quality improvement method: goal setting regarding preventive care, assessment of current preventive care processes and level of goal attainment, planning to modify existing routines and to implement improved routines that support preventive care, and starting and maintaining the improved practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors have identified that women often forget when screening is due and, therefore, inadvertently neglect timely screening (McPhee et al. 2002, Backer et al. 2005, Lovell et al.…”
Section: Literature Reviewmentioning
confidence: 99%